Research of companies’ bankruptcy and its procedure - Giriūnas, Lukas; Kazlauskas, Aivaras (Buhalterinės apskaitos teorija ir praktika, 2013)
The article examines the companies’ bankruptcy, its procedure and the course of the latter, taking into account the fact that the problem of completion of the bankruptcy procedure has been encountered recently in Lithuania – only one third of the initiated bankruptcy procedures are finished. Such results of the done analysis of statistical data allow stating that the procedure of the companies’ bankruptcy requires for new researches. The main areas of bankruptcy procedure, which have to be improved, were determined and new assessment directions of it were provided. Thus the practical study was conducted in the article in order to learn the course of the bankruptcy procedure and the areas, which need improvement, in Lithuania, and for this purpose the analysis of statistical data and theoretical review of the companies’ bankruptcy were done.
Keywords: companies’ bankruptcy; bankruptcy procedure; bankruptcy case